Предмет: Алгебра,
автор: marmeladnyyche
упс, на помощь........
Приложения:
![](https://files.topotvet.com/i/3bd/3bd13244efe244f9b0fd4b991192b9e3.gif)
Ответы
Автор ответа:
0
Ответ ответ ответ ответ ответ
Приложения:
![](https://files.topotvet.com/i/431/43113567047ccfba1bceabe7f17fac38.jpg)
Автор ответа:
0
(b-3)*(b+1)-(b-6)*(b+6)=
=b^2+b-3b-3-(b^2-36)=
=b^2+b-3b-3-b^2+36
=-2b+33
=b^2+b-3b-3-(b^2-36)=
=b^2+b-3b-3-b^2+36
=-2b+33
Приложения:
![](https://files.topotvet.com/i/431/43113567047ccfba1bceabe7f17fac38.jpg)
Похожие вопросы
Предмет: Литература,
автор: irasimonova2007
Предмет: Математика,
автор: zhannachernova0535
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: artemont22